Information Requirement for Rural Development Through Telecentre in Kaduna State, Nigeria - Dogara, Mohammed Aliyu (2011)
Rural information telecentre content play major a role in information dissemination for the rural farmers. Telecentre information content system is a device in ICT that used to alert rural people to know what is going on in the community and updating them about improvement in their daily activities livelihood. This research work address the objectives of user requirement needs for rural ICT, in community development centers in south and north of Kaduna Nigeria. General research method was used. The prototype of telecentre content system was developed with the use of PHP, Java script for the programming language and micro media directory, Xamp as well as Adobe Photoshop. Ten people tested the usability of prototype. The developed telecentre content system brings about adequate information about their daily need when compare to previous way of life and improve the rural farmers to have basic knowledge in using computer. With the use of this device, positive turn around will manifest in Kaduna rural livelihood and increase in income level through market information alert.